Economic Diversification In Iraq: A Comprehensive Review - Aras Abdulkareem Miho (Universitas Palan, 2024)
Economic diversification is crucial for Iraq to overcome the limitations imposed by its heavy reliance on oil. This study explores Iraq's economic history, current structure, and the urgent challenges it faces, emphasizing the need for structural transformation. It examines the vulnerabilities caused by fluctuating global oil prices, geopolitical instability, and internal demographic pressures for the period of 2004 to 2022. By analyzing government policies, sectoral developments, and international collaborations, this research highlights the efforts and obstacles in achieving economic diversification. The findings indicate that while Iraq has made strides toward diversifying its economy, it still faces significant challenges such as bureaucratic inefficiencies, political instability, and security concerns. International collaborations and foreign direct investment (FDI) emerge as crucial components, providing the financial support and technological expertise needed for economic transformation. Lastly, economic diversification is more than just an economic strategy for Iraq; it is a comprehensive approach to achieving long-term stability and growth. A diversified economy can help Iraq build resilience against external shocks, promote inclusive growth, and secure a sustainable and prosperous future. The imperative for economic diversification is clear: to create a stable, balanced, and resilient economy that can withstand global market fluctuations and geopolitical dynamics, ultimately improving the well-being of its population